Thermal-Energy Performance of High-Albedo Roof Tiles and Bulk Rafter Insulation in Residential Roof in the Tropical Climate - Farhan, S.A. (IOP Publishing Ltd, 2021)
Residential roof assemblies in tropical countries, such as Malaysia, are exposed to intense solar radiation throughout the day all-year round due to the high altitude of the sun path as well as the horizontal orientation and high position of the roof in relation to other components of the building envelope. Residential buildings typically employ a lightweight pitched roof with roof tiles and an attic space above a ceiling board. Diurnal heat transfer into the building through the roof assembly can be minimized by reflecting heat at the roof surface via the application of white paint on high-albedo roof tiles as well as resisting heat via installation of bulk rafter insulation within the roof assembly. However, their adoption will have an influence on the nocturnal heat transfer and, accordingly, the resultant thermal-energy performance. Hence, thermal-energy performances of high-albedo roof tiles and bulk rafter insulation were compared to develop an energy-efficient pitched residential roof assembly that is capable of minimizing diurnal heat transfer into the building with less obstruction of the nocturnal heat transfer in the opposite direction. Evaluation of thermal-energy performance was performed on a Building Information Model, which either adopts, solely, the application of white paint on high-albedo roof tiles, or, in amalgamation with, the installation of bulk rafter insulation within the roof assembly. The simulation projected that the application of white paint on high-albedo roof tiles can generate annual energy savings of 13.14 and, when adopted in amalgamation with the installation of bulk rafter insulation within the roof assembly, 13.91 . Â© Published under licence by IOP Publishing Ltd.